Citizens perceptions of urban freight transport: an international comparison - João Guilherme da Costa Braga França; Kinga Kijewska; Stanislaw Iwan; Cassiano Augusto Isler; Leise Kelli de Oliveira (Transportation Research Interdisciplinary Perspectives)
Urban freight transport is essential for cities as it facilitates the delivery of goods and services to meet stakeholder needs. However, it also creates challenges, including congestion, parking space occupation, pollution, and accidents involving freight vehicles. This paper employs partial least squares structural equation modeling to explore the cause-and-effect relationships between urban freight transport issues and initiatives from the citizens’ perspective. The study analyzes six causal relationships in two cities – Belo Horizonte, Brazil, representing the Global South, and Szczecin, Poland, representing the Global North – while considering their geographic, socioeconomic, and political contexts. The findings reveal that citizens’ perceptions of freight-related issues influence their views on city logistics initiatives and their perceived effectiveness In Belo Horizonte, infrastructure problems, particularly those related to pedestrian and cyclist safety, are considered more significant compared to Szczecin, where environmental issues, such as pollution, have a more prominent latent perception. The comparative analysis underscores causal relationships between urban flow challenges and freight problems, demonstrating that urban flow issues are more critical than infrastructure or environmental concerns in both cities. Differences also emerge in the perceived effectiveness of initiatives: while truck restrictions are highly valued in Belo Horizonte, loading and unloading areas and clearer signage are more impactful in Szczecin. Green initiatives show potential for promoting sustainable urban freight transport in both contexts. However, the limited variability in citizens’ responses, particularly in Szczecin, suggests a consensus on the relevance of the proposed initiatives. The results offer dual benefits: providing direct recommendations for Belo Horizonte and serving as a benchmark for Szczecin and other cities adopting an adaptive approach to urban logistics. These insights can guide policymakers in fostering efficient and sustainable urban freight transport through a participatory planning process in Global South and North.